Urgency in Anti-Corruption Education Course in University and Civil Law Review - Imam Subiyanto (LEGAL BRIEF, 2021)
As a state of law that is always obedient and obedient to every policy of its government, the state of Indonesia is one of the countries that is still weak in monitoring various legal actions that occur in various layers of society and government institutions. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the law of criminal acts of corruption is a legal aspect that must undergo various improvements as a whole, and one of them is the government through a presidential decision issued an idea in order to fulfill the character of students. In order to understand further the development of corruption cases in Indonesia and how to overcome them, then by implementing anti-corruption education at various levels of formal education in Indonesia, it is possible to reduce the number of corruption cases in Indonesia and shape the character of the nation's next generation to be superior, creative and uplifting. high values of kindness and honesty.